A routine combining motivational self-talk and mental imagery improves service performance - Dominique, L.; Robin, N. (Coaching and Sport Science Review, 2024)
The aim of this study was to test the effects on the performance of experienced tennis players of a service pre-performance routine consisting of internal motivational discourse combined with mental imagery centred on the trajectory of the ball and the target zone to be reached in the service box. Twenty-seven male players (M = 17.5 years) from the second series (ranked between 5/6 and 3/6), who had been playing tennis for more than 10 years, volunteered to take part in this experiment. The participants were divided into 3 groups (control, discourse, and discourse + imagery) and carried out 3 phases: Pre-test (20 serves in playing condition), Acquisition: 16 sessions (warm-up + 20 serves + super tie-break), Post-test (20 serves in playing condition). The percentage of success, speed and efficiency of the serves were measured at the Pre- and Post-tests and served as dependent variables for statistical analyses (repeated measures ANOVAS). The results of this study show a further improvement in serve performance when internal motivational discourse is combined with mental imagery. We recommend that experienced tennis coaches and players use internal self-talk as well as imagery in their pre-serve performance routines.